2012
DOI: 10.1017/s0007114511006878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-dose fish oil supplementation during early infancy on neurodevelopment and language: a randomised controlled trial

Abstract: n-3 Long-chain PUFA (LC-PUFA) intake during infancy is important for neurodevelopment; however, previous studies of n-3 LC-PUFA supplementation have been inconclusive possibly due to an insufficient dose and limited methods of assessment. The present study aimed to evaluate the effects of direct supplementation with high-dose fish oil (FO) on infant neurodevelopmental outcomes and language. In the present randomised, double-blind, placebo-controlled trial, 420 healthy term infants were assigned to receive a DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 61 publications
3
70
0
1
Order By: Relevance
“…Another Swedish cohort study [34] of moderately preterm infants found positive associations between both AA and DHA in infant blood and global developmental outcomes at 18 months of age, but negative associations with n-6 PUFA and the n-6/n-3 PUFA ratio. The observed assocition between AA and language skills is in accordance with some previous studies of term infant showing negative associations between LC-PUFA intake or status and language development [26,46], but other studies found no effect [47,48]. The previous studies have primarily focused on the effect of supplementation with fish oil, DHA or DHA+AA.…”
Section: Discussionsupporting
confidence: 90%
“…Another Swedish cohort study [34] of moderately preterm infants found positive associations between both AA and DHA in infant blood and global developmental outcomes at 18 months of age, but negative associations with n-6 PUFA and the n-6/n-3 PUFA ratio. The observed assocition between AA and language skills is in accordance with some previous studies of term infant showing negative associations between LC-PUFA intake or status and language development [26,46], but other studies found no effect [47,48]. The previous studies have primarily focused on the effect of supplementation with fish oil, DHA or DHA+AA.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have evaluated mental development, visual acuity, or motor development during infancy or in young childhood and the results have been mixed: one study providing high-dose fish oil with n-3 LC-PUFA but without AA did not observe beneficial effects on Bayley Scale of Infant Development (BSID) scores [87], one observed a beneficial effect on the mental development index [85], and another study reported beneficial effects on visual acuity [86] when 3 different DHA dosage groups were combined. These data may indicate that effects at younger ages may be too subtle to detect with smaller sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Moderate to late preterm birth increases the risk of neurodevelopmental problems [21]. Although supplementation of high-dose omega-3 fatty acids has not been shown to improve global development [22], it is plausible that the normal physiological acquisition of omega-3 fatty acids in late gestation is neuroprotective. The role of omega-3 fatty acids in overweight and obese adults is less clear.…”
Section: Discussionmentioning
confidence: 99%